Political science and the three new institutionalisms - Hall, P. G. (Peter Geoffrey) 1932- (Max-Planck-Institut für Gesellschaftsforschung, 1996)
The new institutionalism is a term that now appears with growing frequency in political science. However, there is considerable confusion about just what the new institutionalism is, how it differs from other approaches, and what sort of promise or problems it displays. The object of this essay is to provide some preliminary answers to these questions by reviewing recent work in a burgeoning literature.